MEAT FROM HOME: MODES AND MEANINGS OF MEAT PRODUCTS FLOW FROM DAGESTAN TO THE CITIES OF THE RUSSIAN ARCTIC - Kapustina, Ekaterina Leonidovna (History, Archeology and Ethnography of the Caucasus, 2022)
The translocality of labor migration between the Republic of Dagestan and the Arctic and subarctic cities of Western Siberia gives rise to specific practices of materiality associated with the transportation of things between the sending and receiving parties. Food products occupy the most prominent place in this line both in terms of the scale of transfers and in terms of their importance in the daily life of migrants from Dagestan in northern cities. The article analyses various options and mechanism of transportation of meat and meat products via Dagestan migration networks. We pay close attention to the transportation of meat as a multi-stage process – from purchasing it in Dagestan to organizing a storage system in a migrant family. In this case, both commercial transfers and family and compatriot parcels will be of interest, since in both cases similar schemes are used and the same networks are involved. Meat, intended primarily for migrants, becomes a “migrant” itself in the process of shipment; its appearance in the place of migration is endowed with meanings and characteristics associated with migration between these regions as a whole. Through the role and scale of the use of Dagestan meat in the daily migrants’ diet, one of the aspects of constructing the translocal world of Dagestanis working in Arctic cities is demonstrated. In particular, of interest are the reciprocity mode both within the migrant community and between migrants and non-migrants in Dagestan, as well as the construction of symbolic representations of an abandoned house and a house built in migration, reflection on the degree of complementarity of the material worlds of Dagestan and the North, their fundamental differences and benefits.